The Digital Dilemma: How Technostress and Digital Competence Impact Employee Performance via Job Satisfaction - Syahputra, Muhammad Dio; Rahmawati, Rini; Claudia, Meiske; Rifani, Ahmad (Cita konsultindo, 2025)
This study delves into the critical relationship between technostress, digital competence, and employee performance at PT Air Minum Bandarmasih (Perseroda), with job satisfaction as a key mediating variable. The primary objective is to address the gap in existing research by examining how these technological factors influence employee outcomes within the specific context of a state-owned water utility company. Using a quantitative approach with a sample of 146 staff-level employees, the study employs Proportionate Stratified Random Sampling and SEM-PLS analysis to build upon previous studies by providing a nuanced understanding of these dynamics. The findings offer a significant novelty by confirming the negative and significant impact of technostress on both job satisfaction and performance, while simultaneously highlighting the positive and significant effect of digital competence. Crucially, the research establishes the vital role of job satisfaction as a mediator, demonstrating that managing technological demands and enhancing digital skills are not just about efficiency but are foundational to fostering employee well-being and, consequently, improving overall performance in the digital era.